PEMANFAATAN AIR HUJAN BERSIH DAN LAYAK MENGGUNAKAN ALAT FILTRASI SEDERHANA DI TAMAN PEGELARAN CIOMAS BOGOR - Budiman, Budiman; Aminda, Renea Shinta; Syaiful, Syaiful (JPMUJ, 2023)
Utilization of rainwater will basically help meet daily water needs, by utilizing rainwater it is expected to reduce the cost of water needs, especially for areas that lack clean water due to a small quantity of ground water or poor water quality. The water used must of course be clean and proper water, in accordance with the law governing water resources, namely Law Number 17 of 2019, So in addition to utilizing rainwater, a simple filtration tool is needed that is useful for filtering water so that the water is clean. and safe, besides being used to filter dirty/muddy water, this filtration can also be used to reduce the level of Fe contained in water by utilizing gravel, sand and activated activated carbon.